Effect of Calcium and Manganese Supplementation on Heat Resistance of Spores of Bacillus Species Associated With Food Poisoning, Spoilage, and Fermentation - Sinnelä, Martti Tapani; Pawluk, Alixander Mattay; Jin, Young Hun; Kim, Dabin; Mah, Jae-Hyung (Frontiers in Microbiology, 2021)
Bacterial spores often survive thermal processing used in the food industry, while heat treatment leads not only to a decrease in the nutritional and organoleptic properties of foods, but also to a delay in fermentation of fermented foods. Selective reduction of undesirable spores without such impediments is an ongoing challenge for food scientists. Thus, increased knowledge of the spore-forming bacteria is required to control them. In this study, the heat resistance results (D100°C) of the spores of four Bacillus species were determined and compared to previous literature, and found that B. cereus has significantly lower heat resistance than the other Bacillus species, B. coagulans, B. subtilis, and B. licheniformis. Using the spores of these strains, this study also evaluated the effects of single and combined supplementation of calcium (0.00–2.00 mM) and manganese (0.00–0.50 mM) on heat resistance (D100°C). The results revealed that the spores of B. licheniformis and B. cereus displayed the smallest heat resistance when sporulated on media rich in calcium. Conversely, B. coagulans spores and B. subtilis spores exhibited the greatest heat resistance when sporulated under calcium-rich conditions. The opposite results (stronger heat resistance for B. licheniformis spores and B. cereus spores, and smaller heat resistance for B. coagulans spores and B. subtilis spores) were obtained when the spores were formed on media poor in the minerals (particularly calcium). Based on the results, the Bacillus species were divided into two groups: B. licheniformis and B. cereus; and B. coagulans and B. subtilis. The study provides valuable insight to selectively reduce spores of undesirable Bacillus species in the food industry.